2016
DOI: 10.1080/1067828x.2015.1066722
|View full text |Cite
|
Sign up to set email alerts
|

Person-Environment Interactions and Adolescent Substance Use: The Role of Sensation Seeking and Perceived Neighborhood Risk

Abstract: Aims: This longitudinal study investigated person-environment interactions and adolescent substance use by examining whether, and if so how, early temperamental quality of sensation seeking interacted with current neighborhood characteristics to shape underage smoking, drinking, and marijuana use. Sample: Participants consisted of a community-representative sample of 352 adolescents. Methods: Early temperament was assessed when adolescents were between seven and 13 years of age, and current neighborhood charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…No research to our knowledge has examined whether the interaction between community disadvantage and an internalizing symptoms PRS is associated with the development of alcohol-related disorders. However, our results are consistent with limited research linking temperamental inhibition (a potential phenotype of internalizing symptoms) and community disadvantage to alcohol use (Andreas & Watson, 2016). Findings from this study indicated that greater exposure to neighborhood problems was associated with heavier alcohol consumption among individuals lower in temperamental inhibition (Andreas & Watson, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…No research to our knowledge has examined whether the interaction between community disadvantage and an internalizing symptoms PRS is associated with the development of alcohol-related disorders. However, our results are consistent with limited research linking temperamental inhibition (a potential phenotype of internalizing symptoms) and community disadvantage to alcohol use (Andreas & Watson, 2016). Findings from this study indicated that greater exposure to neighborhood problems was associated with heavier alcohol consumption among individuals lower in temperamental inhibition (Andreas & Watson, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Parental behaviors may promote the maturation of reward sensitivity, sensation seeking, and risk‐taking behaviors by possibly denying access to risk‐taking opportunities at a young age, or by potentially channeling sensation seeking toward more pro‐social rewards. Recent studies have found that neighborhood disadvantage moderates the relationship between sensation seeking and substance use largely via the provision of additional risk‐taking opportunities (Burdzovic Andreas & Watson, ; Jensen, Chassin, & Gonzales, ). In contrast to this research, it should be noted that most studies that have examined the relationship between sensation seeking and parental behaviors have failed to find a significant interaction (e.g., Janssen et al., ; Kaynak et al., ).…”
Section: Discussionmentioning
confidence: 99%